2022
DOI: 10.1097/sap.0000000000003195
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Access to Postmastectomy Breast Reconstruction: Does Living in a Specific ZIP Code Determine the Patient’s Reconstructive Journey?

Abstract: Background Postmastectomy breast reconstruction (BR) has been shown to provide long-term quality of life and psychosocial benefits. Despite the policies initiated to improve access to BR, its delivery continues to be inequitable, suggesting that barriers to access have not been fully identified and/or addressed. The purpose of this study was to assess the influence of geographic location, socioeconomic status, and race in access to immediate BR (IBR). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…3). This is consistent with recently published reports that cite Black women have significantly lower reconstruction rates (35% vs 49%) when compared with White women, and when reconstruction is pursued it is more commonly autologous reconstruction (13% vs 7%) 18–20 . The type of reconstruction treatment chosen may reflect patient preferences, attitudes toward reconstruction, cultural beliefs, and bias among providers.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…3). This is consistent with recently published reports that cite Black women have significantly lower reconstruction rates (35% vs 49%) when compared with White women, and when reconstruction is pursued it is more commonly autologous reconstruction (13% vs 7%) 18–20 . The type of reconstruction treatment chosen may reflect patient preferences, attitudes toward reconstruction, cultural beliefs, and bias among providers.…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with recently published reports that cite Black women have significantly lower reconstruction rates (35% vs 49%) when compared with White women, and when reconstruction is pursued it is more commonly autologous reconstruction (13% vs 7%). [18][19][20] The type of reconstruction treatment chosen may reflect patient preferences, attitudes toward reconstruction, cultural beliefs, and bias among providers. Although implant-based reconstruction was found to be the most common overall treatment option in our patient population, several studies have shown that autologous reconstruction has preferred outcomes.…”
Section: Discussionmentioning
confidence: 99%